Development of a Problem Based Learning Model Physics Learning Module to Increase High School Students' Interest in Learning Physics - Rini, Theresia Nona; Koten, Florentinus P. N; Sahlan, Sahlan (Lembaga Riset Mutiara Akbar, 2023)
This study aims to produce a feasible PBL model physics module to increase interest in learning the cognitive domain of high school students and determine the increase in students' interest in learning physics after using the PBL model physics module. This research was conducted at St. Petrus Kewapante High School in class X majoring in Science. The method used is a research method with a quantitative approach that is descriptive statistics. The results of the study obtained that the resulting PBL model physics module is suitable for use to improve learning in the cognitive domain of high school students based on the assessment of the material expert validator has an average value of 92% with very good quality criteria and media experts have an average value of 93%. with very good quality criteria. The use of the PBL model physics module on Newton's Laws of motion is able to increase students' interest in the physics subject of class X IPA students. From the results of the questionnaire results of students' interest in the PBL model physics module, an average score of 92% was obtained with very good quality criteria.